Thermodynamic Analysis of Gas Turbine Power Plant of PT PLN Belawan Generation Implementation Unit - Sofyan, Sarwo Edhy; Umar, Hamdani; Tamlicha, Akram; Ramafunna, Fitra Ilham (Jurnal Polimesin, 2024)
The low quality of the thermodynamic process in a gas turbine power plant results in the waste of potential energy and impacts the power plant's efficiency. Analysing the thermodynamic performance of a gas turbine power plant is crucial to evaluating its efficiency in converting fuel energy into useful work. This analysis helps identify opportunities for improvement and optimise the plant's design for better performance by examining the components (e.g., the compressor, combustion chamber, and turbine). This study aims to evaluate the performance of a Gas Turbine Power Plant (GTPP) through thermodynamic analysis considering the variation of cycle loads. The study was conducted based on the field survey data obtained from the GTPP PT PLN Belawan generation implementation unit. The collected operation data was used to perform a thermodynamic analysis by applying the principles of conservation of mass and energy, along with the laws of thermodynamics. The study examined five cycle load variations: 31.7 MW, 34.3 MW, 48.1 MW, 60.7 MW, and 71.7 MW. Results showed a consistent reduction in the gas turbine heat rate as the load increased, with a significant 53.3% drop in heat rate from 34.3 MW to 71.7 MW. Higher cycle loads also correlated with increased turbine and compressor work, with the turbine producing 55.8% more work than the compressor at 71.7 MW. The turbine's thermal efficiency ranged from 40% to 44%, with potential for a 5% efficiency increase.